Regulatory Gaps In Copyright Protection For NFT-Based Digital Artworks In Indonesia - Aditya Pangestu Nugroho; Hastarini, Arvita (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2025)
This research analyzes the legal protection mechanisms for digital illustration copyrights in the NFT market in Indonesia so that the public's limited knowledge about copyrights can lead to many problems, such as effectively addressing digital art theft. Besides the types of digital art that are still unfamiliar to the Indonesian public, plagiarism is one of the biggest threats to digital artists. Because the internet is vast and easily accessible, it is easier for a digital artwork to be stolen without the creator's knowledge. Some key issues that will be discussed in this scientific paper are the protection of copyright for digital art as one of the copyrights that must be protected, as well as the implementation issues of protecting digital art against attempts to use these works without permission. Using a normative juridical method. The results of the research and discussion conclude that legal protection for digital art is implicitly regulated under Law Number 28 of 2014 concerning Copyright. Starting from the protection of the creator's exclusive rights to the legal actions that can be taken by the creator of the work. Keywords: Intellectual Property, NFT Marketplace, The Legal Protection